2016
DOI: 10.1002/9781119078289
|View full text |Cite
|
Sign up to set email alerts
|

Enabling Technologies for High Spectral‐Efficiency Coherent Optical Communication Networks

Abstract: Forward error correction (FEC) in optical communications has been first demonstrated in 1988 [1]. Since then, coding technology has evolved significantly. This pertains not only to the codes but also to encoder and decoder architectures. Modern high-speed optical communication systems require high-performing FEC engines that support throughputs of 100 GBit/s or multiples thereof, that have low power consumption, that realize net coding gains (NCGs) close to the theoretical limits at a target bit error rate (BE… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(3 citation statements)
references
References 79 publications
0
3
0
Order By: Relevance
“…The parameters Φ n ch and Φ CUT are the constant Φ used by the EGN model, which depends on the modulation format of a channel [4], [20]. The exact values are shown in Table I, for the modulation formats used in this paper and for PM-BPSK.…”
Section: Cfm2 Derivation and Testmentioning
confidence: 99%
See 1 more Smart Citation
“…The parameters Φ n ch and Φ CUT are the constant Φ used by the EGN model, which depends on the modulation format of a channel [4], [20]. The exact values are shown in Table I, for the modulation formats used in this paper and for PM-BPSK.…”
Section: Cfm2 Derivation and Testmentioning
confidence: 99%
“…12. Plot of the quantity R defined in Eq (20),. representing the ratio between span-by-span increments of NLI as predicted by the EGN model and as predicted by the closed-form model 1 (CFM1).…”
mentioning
confidence: 99%
“…As an example, consider for instance the graphical representation of the entire 14PolSK-8PSK constellation shown in Figure (4). Using the static performance metrics presented in Table (I) [ 31], where M is the number of constellation points, N is the dimension of the modulation, d is the minimum (Euclidean) distance between symbols, E b is the energy per bit and E is the average energy per symbol. We have found that for the…”
Section: Qam Partitions and The Cayley-dickson Representation For mentioning
confidence: 99%